Roadmate: improving ridesharing and carpooling via mobile app / Muhammad Farid Muhammad Dahri, Arifah Fasha Rosmani - Muhammad Dahri, Muhammad Farid; Rosmani, Arifah Fasha (College of Computing, Informatics and Media, UiTM Perlis, 2023)
The practice of carpooling involves several persons traveling in the same vehicle. Carpools help people save money on gas and cut down on carbon emissions. Typically, they are organized by people or businesses. Compared to more traditional ehailing applications, many users urge a ridesharing and carpooling apps to be released. People can save money by ridesharing and carpooling. Hence, the RoadMate app tend to makes it simple for drivers to find new passengers and vice versa. Instead of utilizing ehailing alone, people can save time and money by using this app. Carpooling also lessens traffic and air pollution by lowering the number of vehicles on the road.